MULHERES NOS TERREIROS DA ESPERANÇA: ANCESTRALIDADES NO QUILOMBO URBANO DA BOA ESPERANÇA, EM TERESINA/PI - de Sousa Rego , Natasha Karenina; Ferreira do Nascimento, Elaine (Entropia, 2025)
The research aims to answer the problem: how are ancestries perceived by the residents of Quilombo Urbano da Boa Esperança in Teresina, Piauí?, with the general objective of reflecting on what is perceived as ancestries by the Quilombo and specific objectives: situating the Boa Esperança community as traditional and quilombola; conceptualize ancestries based on escrevivências [writing-living]; identify how ancestries are perceived by residents. The study is exploratory, descriptive, documentary and bibliographic, with a qualitative approach, intersectional focus and the contribution of writing. Data were extracted from the Women’s Project in Terreiros da Esperança video, analyzed through observation and interpretation of statements with intersectionality. It is noted that the residents, even before the community claimed to be quilombola, already perceived their ancestries as indigenous and African, expressed in the permanence of the territory and ways of life.